Languaging and written corrective feedback in L2 writing - Sabariah Abd Rahim; Irma Wani Othman; Anna Lynn Abu Bakar; Bernadette Tobi (Global Academic Excellence, 2022)
The aim of this article is to introduce the application of languaging as the mediational tool to enhance the written corrective feedback’s effectiveness in L2 writing. Written Corrective Feedback (WCF) shows L2 learners their grammatical and ungrammatical errors in writing. It is a form of feedback that is commonly applied pedagogically in writing class. With WCF, L2 learners can improve their ability to write without errors. Nevertheless, providing WCF alone without engaging L2 learners will make the L2 learners become passive learners. They merely copy their teachers’ WCF where they can neither identify nor correct their errors. Therefore, it is recommended that L2 learners are given the opportunity to engage (to notice and understand) with the WCF. Languaging creates the opportunity for L2 learners to engage with the teachers’ WCF. Languaging is a process where L2 learners make meaning, shape knowledge and experience through language. L2 learners use language (languaging) to solve difficult task like L2 writing. When L2 learners languaging the teachers’ WCF, they should be able to improve their writing skills. This paper has pedagogical implications in L2 writing.